2007
DOI: 10.1038/sj.leu.2404988
|View full text |Cite
|
Sign up to set email alerts
|

Pim2 complements Flt3 wild-type receptor in hematopoietic progenitor cell transformation

Abstract: Pim2 is a serine/threonine kinase expressed at high levels in several malignancies including acute leukemia. Pim2 protein is induced by oncogenic Fms-like tyrosine kinase-3 (Flt3)-internal tandem duplications (ITD), but not by Flt3 wild-type receptor (Flt3-Wt) in response to Flt3 ligand (FL). Here we show that Pim2 can complement Flt3-Wt signaling and induce transformation similar to Flt3-ITD in myeloid cells. Our data demonstrate that Pim2 is necessary but not sufficient for Flt3-ITD-induced transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…67 In cellular models of malignant myeloproliferative disorders, PIM1 and PIM2 were both found to be up-regulated and proposed to be a mediator of anti-apoptotic properties of oncogenic protein tyrosine kinases (PTKs) such as BCR/ABL, FLT3-ITD, or the JAK2V617F mutant, most probably mediated through aberrant JAK2/STAT5 activity. [68][69][70][71][72][73] We and others have observed that overexpression of PIM1 was sufficient to induce IL-3 independence in murine hematopoietic Ba/F3 cells. 74,75 Microarray experiments revealed upregulation of PIM1 expression in acute myeloid leukemia harboring alterations of the mixed-lineage leukemia (MLL) gene such as the MLL/ENL or MLL/AF9 fusion genes 76 (J Schwaller, unpublished observation, 2009).…”
Section: Pim Serine/threonine Kinases In Hematologic Malignancies Andmentioning
confidence: 93%
See 1 more Smart Citation
“…67 In cellular models of malignant myeloproliferative disorders, PIM1 and PIM2 were both found to be up-regulated and proposed to be a mediator of anti-apoptotic properties of oncogenic protein tyrosine kinases (PTKs) such as BCR/ABL, FLT3-ITD, or the JAK2V617F mutant, most probably mediated through aberrant JAK2/STAT5 activity. [68][69][70][71][72][73] We and others have observed that overexpression of PIM1 was sufficient to induce IL-3 independence in murine hematopoietic Ba/F3 cells. 74,75 Microarray experiments revealed upregulation of PIM1 expression in acute myeloid leukemia harboring alterations of the mixed-lineage leukemia (MLL) gene such as the MLL/ENL or MLL/AF9 fusion genes 76 (J Schwaller, unpublished observation, 2009).…”
Section: Pim Serine/threonine Kinases In Hematologic Malignancies Andmentioning
confidence: 93%
“…74,75 Microarray experiments revealed upregulation of PIM1 expression in acute myeloid leukemia harboring alterations of the mixed-lineage leukemia (MLL) gene such as the MLL/ENL or MLL/AF9 fusion genes 76 (J Schwaller, unpublished observation, 2009). Elevated PIM1 levels in acute myeloid leukemia are most likely the consequence of FLT3 activation (by overexpression or mutation) and/or of aberrant activation of HOXA9, a direct transcriptional regulator of PIM1 69,70,72,77 ( Figure 3). To address the role of PIM kinases for induction of PTKmediated leukemic disorders, we have performed bone marrow reconstitution experiments using PIM knockout cells.…”
Section: Pim Serine/threonine Kinases In Hematologic Malignancies Andmentioning
confidence: 99%
“…Supernatants were collected every 12 h, starting 36 h after transfection. For transduction, viruses were bound to RetroNectin-coated plates by centrifugation as described previously (38). Lineage-depleted bone marrow cells were stimulated overnight, transduced by growth on the virus-coated plates for 24 h, and sorted by FACS for EGFP positivity.…”
Section: Methodsmentioning
confidence: 99%
“…Lineage depletion was obtained using the Lineage cell depletion kit, mouse (Miltenyi Biotec, Bergisch Gladbach, Germany), according to the manufacturer's protocol. FACS analyses of spleens were performed as described previously (38).…”
Section: Methodsmentioning
confidence: 99%
“…18 U937 cells were cultured, and treatment with AZA was done as described previously. 19 For Prdx2 knockdown in 32D cells, shRNA oligos were cloned into p-Super-retro puro vector (Oligoengine), and cells were infected with retrovirus produced in PlateE cells as described later.…”
Section: Cell Culture and Materialsmentioning
confidence: 99%